Metabolic dysfunction-associated steatotic liver disease in children - Pawlowska, Malgorzata (Clinical and Experimental Hepatology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is the main chronic liver pathology in children and adolescents. The incidence of MASLD is increasing with the obesity pandemic; MASLD affects approximately 40% of obese children. The article presents diagnostic criteria for MASLD in children, studies of potential screening markers and suggestions for treatment procedures.